Factors influence brand equity of Qu Puteh / Nursyahirah Abu Bakar Azmi - Abu Bakar Azmi, Nursyahirah (Faculty of Business and Management, 2016)
The purpose of this study is, to identify the factors influence brand equity of Qu Puteh among Intekma staff. The research is based on a sample of 36 respondents who is the staff of Intekma Resort. The results show that endorser credibility and self – brand connection influence brand equity of Qu Puteh.